2018
DOI: 10.3390/w10030315
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hydrological Drought in Eastern China Using a Time-Dependent Drought Index

Abstract: Long records (1960Long records ( -2013 of monthly streamflow observations from 8 hydrological stations in the East Asian monsoon region are modeled using a nonstationarity framework by means of the Generalized Additive Models in Location, Scale and Shape (GAMLSS). Modeling analyses are used to characterize nonstationarity of monthly streamflow series in different geographic regions and to select optimal distribution among five two-parameter distributions (Gamma, Lognormal, Gumbel, Weibull and Logistic). Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Since 2012, it has also been recommended by the World Meteorological Organization (WMO) for the operational monitoring of drought threats (World Meteorological Organization (WMO) 2012 ). Two indices are taken as hydrological drought indices: SWI, calculated on the basis of water level WL (Sahoo et al 2015 ), and SRI, based on data for runoff R (Shukla and Wood 2008 ; Mishra and Nagarajan 2013 ; Li et al 2016 ; Ljubenkov and Cindrić Kalin 2016 ; Zou et al 2018 ). The values of the indices used are standardized deviations of precipitation, water levels, and runoff from median values for the long-term period.…”
Section: Climate and Hydrological Datamentioning
confidence: 99%
“…Since 2012, it has also been recommended by the World Meteorological Organization (WMO) for the operational monitoring of drought threats (World Meteorological Organization (WMO) 2012 ). Two indices are taken as hydrological drought indices: SWI, calculated on the basis of water level WL (Sahoo et al 2015 ), and SRI, based on data for runoff R (Shukla and Wood 2008 ; Mishra and Nagarajan 2013 ; Li et al 2016 ; Ljubenkov and Cindrić Kalin 2016 ; Zou et al 2018 ). The values of the indices used are standardized deviations of precipitation, water levels, and runoff from median values for the long-term period.…”
Section: Climate and Hydrological Datamentioning
confidence: 99%
“…It is a tool for modeling and predicting data that are complex, with multiple factors influencing the outcome, and where more insight from each variable is needed than just the central tendency (e.g., the spread and shape of the distribution). A GAMLSS approach, or a variation of it, has been applied to drought analysis, usually to fit precipitation data to a non-stationary gamma distribution (Wang et al 2015;Bazrafshan and Hejabi 2018;Zou et al 2018;Rashid and Beecham 2019b;Das et al 2020Das et al , 2021Wang et al 2022) Established a separation framework including the variable runoff threshold level method and standardized runoff index based on a parameter transplantation method to quantify the impacts of climate change and human activities on hydrological drought and Sung 2022; Blain et al 2022). These studies have shown that series in excess of 30 years can introduce errors in the statistics when stationarity is assumed in a nonstationary dataset (Jehanzaib et al 2021).…”
Section: Statistical Methods To Account For Nonstationarity In Drough...mentioning
confidence: 99%
“…Trend analysis covers both detection and attribution for hydrological drought (Zou et al, 2018). Trends in streamflow have consequences for hydraulic models that are often based on the notion of stationarity that many researchers are now debating because of climate change effects within not only local but also regional climate patterns, or perhaps basin and regional scale (Zeng et al, 2015).…”
Section: Trend Analysismentioning
confidence: 99%